2020
DOI: 10.1080/17441692.2020.1828986
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of human rights in sexual and reproductive health programming: Facilitators and barriers to implementation

Abstract: The need to prioritise those furthest behind is well understood in global health circles, and how human rights norms and standards can help often touted. As rights concerns are particularly recognised in sexual and reproductive health (SRH) programming, as part of a larger exercise, a review was conducted to identify documented barriers and facilitators to implementation. Given the role global guidance plays in implementing rights-based approaches to SRH, UNDP/UNFPA/UNICEF/WHO/World Bank Special Programme of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Many of the issues that surfaced in previous literature reviews were found to translate to SRH research, but additional issues surfaced including a lack of understanding of how to operationalise specific human rights principles, and how to use rights not only as part of the conceptual background to research being undertaken but to practically support research questions and implementation of a research study, as well as the approach taken to data analysis and writing up the work for publication. 9 Further points noted in the literature, and reiterated through the interviews, include the short timeframes imposed by many donors for demonstrating research outcomes, that inhibit the ability to truly understand and write-up the longer-term changes that might be possible through the inclusion of rights. 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many of the issues that surfaced in previous literature reviews were found to translate to SRH research, but additional issues surfaced including a lack of understanding of how to operationalise specific human rights principles, and how to use rights not only as part of the conceptual background to research being undertaken but to practically support research questions and implementation of a research study, as well as the approach taken to data analysis and writing up the work for publication. 9 Further points noted in the literature, and reiterated through the interviews, include the short timeframes imposed by many donors for demonstrating research outcomes, that inhibit the ability to truly understand and write-up the longer-term changes that might be possible through the inclusion of rights. 6 …”
Section: Discussionmentioning
confidence: 99%
“…The literature review noted earlier was used to frame and analyse interview data, including attention to potential tools and approaches to take this work forward. 9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Centre for Reproductive Rights and Vivo Positivo represented Francisca for over a decade to achieve this outcome. Proper investigation of human rights violations is a critical first step in confronting gender‐based violence in institutional settings [ 19 ].…”
mentioning
confidence: 99%